Technology readiness, information and communication technology (ICT) competency, and the nature and pattern of ICT utilizing among nurses of a tertiary hospital - Formoso, Juanito H. Jr. (Thesis -- (Master of Arts in Nursing) -- University of the Philippines Manila.)
This study aimed to develop a technology integration profile among nurses, which will contribute to the development of a knowledge base that will facilitate the understanding of ICT integration within the Philippine healthcare delivery system especially on a nursing perspective. Elements of this profile includes the technology readiness level, ICT competency level and the relationship of these constructs with the nature and pattern of ICT utilization among nurses.
Utilizing a descriptive correlation design, 174 nurses from the Nurse I to VI position levels from a tertiary government hospital were selected through stratified random sampling technique. A four part self administered questionnaire was used to quantitatively determine and measure the variables in the study.
Results showed that majority of the respondents were skeptical in terms of technology readiness, has intermediate ICT competencies, uses a variety of ICT devices and equipment, and were selective in the utilization of ICT in the workplace due to several institutional factors.
Various issues and concerns were identified, wherein several stratifies were recommended in order to realize and optimize the potentials of ICT integration in professional nursing practice.
Keywords: Information and Communication Technology; Technology readiness; ICT Utilization